2014
DOI: 10.1002/anie.201404410
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (±)‐Tetrapetalone A‐Me Aglycon

Abstract: The first synthesis of (±)-tetrapetalone A-Me aglycon is described. Key bond-forming reactions include Nazarov cyclization, a ring-closing metathesis (RCM) promoted with complete diastereoselectivity by a chiral Mo-based complex, tandem conjugate reduction-intramolecular aldol cyclization, and oxidative dearomatization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 90 publications
0
37
0
Order By: Relevance
“…When aryl enone 16b was subjected to Cu 2+ catalysis, cleavage of the TMS group occurred, presumably due to trace Bronsted acid present in the reaction mixure (entry 3) 19 . This convenient desilylation facilitated the ring-closing metathesis studies that led to the formation of the C ring 13 . Indanone 18b was isolated (in crude form) as a 3:1 mixture of trans:cis isomers (see experimental section).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…When aryl enone 16b was subjected to Cu 2+ catalysis, cleavage of the TMS group occurred, presumably due to trace Bronsted acid present in the reaction mixure (entry 3) 19 . This convenient desilylation facilitated the ring-closing metathesis studies that led to the formation of the C ring 13 . Indanone 18b was isolated (in crude form) as a 3:1 mixture of trans:cis isomers (see experimental section).…”
Section: Resultsmentioning
confidence: 97%
“…Using the protocol of Stradiotto, 25 we were able to cross-couple ammonia to aryl bromide 25 to furnish aniline 36 in 97% yield (entry 9). In a previous report, we successfully elaborated aniline 36 into tetrapetalone A-Me aglycon ( 6 ) 13 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…256) [665], homoisofagomines and analogs [666], cycloheptenes derived from two proline units [667], tuberostemospiroline and stemona lactone R [668], a cyclic α-amino acid derivative (e.g. 257) [669], tetrapetolone (through a diastereoselective RCM employing a substrate with diastereotopic vinyl groups using a chiral molybdenum complex catalyst) [670], and tricyclic IAP inhibitors (e.g. 258) [671]; (14) seven-and eight-membered ring allylic amines (and related acyclic allylamines through cross metathesis) [672]; (15) seven-and eight-membered ring cyclic hydrazines (e.g.…”
Section: )mentioning
confidence: 99%
“…This metabolic network forms signaling molecules such as leukotrienes, lipoxins, and prostaglandins, which have been shown to be involved in the development of a variety of human diseases. 188 During studies toward the synthesis of tetrapetalone A-Me aglycon (150), Frontier and co-workers 189,190 found that hydrogenation of substituted pyrroles such as 151 (Scheme 35), which incorporate an α-keto ester substituent at the 2-position, led to the reduction of both the ketone and the pyrrole ring with high diastereoselectivity to form the corresponding amine 152 [diastereomeric ratio (dr) > 20:1]. This impressive transformation was achieved with 5 mol % Rh/ Al 2 O 3 as the active catalyst at elevated pressures with hydrogen gas.…”
Section: Haouamines a And Bmentioning
confidence: 99%